(untitled) (Journal of Ideas in Health, 2025)
Background: The inappropriate use of antibiotics remains a critical driver of antimicrobial resistance (AMR), posing a significant threat to global public health. Poor adherence to antibiotic prescribing guidelines among healthcare providers contributes to the development and spread of resistant bacterial strains. In Iraq, the extent of this problem, particularly in primary healthcare settings, remains underexplored. This study aimed to assess the knowledge, attitudes, and practices of physicians regarding antibiotic prescription guidelines in primary healthcare centers (PHCs) in Ramadi, Iraq. Methods: A cross-sectional study was conducted between January and March 2024 among 92 doctors working in PHCs in Ramadi. Data were collected through a structured questionnaire assessing sociodemographic characteristics, knowledge, and attitudes toward antibiotic use. Descriptive and inferential statistical analyses were performed using SPSS version 26. Results: Among 92 respondents, 52.2% were female, and the majority had less than two years of experience. Although 77.2% reported that their facility provided antibiotic guidelines, only 46.7% had received regular training. Notably, 98.9% acknowledged that misuse of antibiotics contributes to resistance. However, 28.3% still believed antibiotics were effective against viral infections. Attitudes showed that 65.2% consult infectious disease experts before prescribing broad-spectrum antibiotics. Conclusion: The study highlights moderate awareness but variable adherence to antibiotic prescription guidelines among doctors in Ramadi PHCs. Interventions focusing on continuous training, access to updated guidelines, and multidisciplinary support are essential to enhance rational antibiotic use.